Interconnections between Culture, Tourism, and Economy: A Bibliometric Literature Review with Implications for Sustainable Development - Sutawan, I Wayan Pande; Susilowati, Indah; Prastyadewi, Made Ika (Universitas Pendidikan Ganesha, 2025)
This study refers publication trends related to culture, tourism, and economy to construct the basis for further research. The analysis employed a literature review by utilizing VosViewer software. Articles were sourced from Scopus with the criteria: published between 2020–2025, in English, and including the keywords culture, tourism, and economy. Articles with the highest number of citations relevant to the requirements were discussed further. The results of document searches in Scopus showed that there were 674 documents with the keywords culture, tourism and economy. Most publications originated from East Asia and North America. The development ofpublicity related to culture, tourism and economy will generally include local wisdom as a tourist attraction. These findings reveal the increasing scholarly attention on the interplay between culture, tourism, and economy, particularly concentrated in East Asia and the USA, highlighting significant opportunities for sustainable cultural tourism development, especially in under-researched regions such as Indonesia. Most publicity mentions that over time there has been a shift in culture, the majority of which leads to negativity. This result then becomes an important topic related to the sustainability of culture in the economy, especially when the culture becomes atourist attraction.